Menghadapi Krisis Pendidikan Indonesia: Perspektif Thomas Kuhn Mengenai Revolusi Paradigma - Riyadi Rafiki; Yusuf Tri Herlambang (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Indonesia's education system is facing a crisis that represents one of the most significant challenges in achieving a globally competitive society. This issue has evolved into an anomaly and even a crisis, encompassing aspects such as teaching quality, infrastructure, and the lack of curriculum relevance to contemporary challenges and demands. These factors highlight the urgent need for systemic reform and comprehensive transformation in education to cultivate a generation that is excellent, competent, globally competitive, and, most importantly, possesses noble character. This study aims to examine the crises in the education sector and explore innovative solutions to address these challenges through Thomas Kuhn's perspective on paradigm revolutions. The research employs a literature review method (library research) to source relevant and high-quality materials to produce a well-founded analysis. The findings reveal that various small paradigms have been proposed to address the existing education crisis in Indonesia. These emerging paradigms offer incremental solutions to tackle the issues within the education system, though they have yet to establish a new normal science framework.